The Exploration of Students’ Perceptions of Using the EWA Application for Learning English Vocabulary at SMA Negeri 15 Padang - Zahra, Afifah; Hanifa, Rizaldy (Journal of English Language Teaching, 2024)
This research aimed to explore students’ perceptions of using the EWA application as a learning media in learning vocabulary. The research employed a descriptive qualitative approach to depict the experiences of the research subject. The research participants were 32 senior high school students of eleventh in 2023/2024 the academic year. The data were collecting by using questionnaires and interviews. The findings showed that majority of students had positive perception in using the EWA application for learning vocabulary. In addition, students felt interested and motivated in learning English, especially vocabulary, because it provides exciting pictures, video, and games that makes they enjoy using it anytime and anywhere. Besides that, the data revealed that students encounter challenges with their internet connection while using the application. Therefore, teachers and schools play a crucial role in helping students utilize their educational application such as EWA as learning media in the process of learning English vocabulary. It was recommended for students to be able in utilizing EWA inside or outside the classroom and for next researcher can utilize the EWA app in other language skills through a wider sample.